Mental Status and Quality of Life in Patients With Sinus Node Weakness Syndrome and Chronic Coronary Heart Failure of Ischemic Etiology (Texas Journal of Medical Science, 2022)
The frequent combination of sinus node weakness syndrome (SNWS) and chronic heart failure (CHF) in patients has shown the need for a comprehensive study of their impact on the adaptability of these patients. The assessment of quality of life (QOL) and mental status in patients with SNWS and CHF of ischaemic etiology was carried out. Sinus node weakness syndrome accounts for about 9% of all cardiac rhythm disorders and is one of the current problems of modern arrhythmology. This is due to the fact that with sinus node weakness syndrome hemodynamic disorders can develop, the quality of life of patients is reduced, significant difficulties arise in the treatment of the underlying cardiovascular disease and associated rhythm disturbances. Patients with sinus node weakness syndrome have a reduced ability to work. For example, 14.5% of all patients with a first-time disability are with sinus node disorder. In industrialised countries, more than half of the patients implanted with an artificial pacemaker are patients with weak sinus node syndrome. We used 6 minute walking test, as well as level of depression, anxiety, alexithymia; coping>mechanisms and Vital Style Index in 75 CHD patients with and without SNWS, complicated CHF I>II (NYHA) were assessed. No additional negative effect of SNWS on somatic, mental status and QOL was found in patients with CHF